Late early Miocene mammals from Laguna del Laja, Cura-Mallín Formation, south-central Chile ( 37°S) and their biogeographical and paleoenvironmental significance. (December 2021) - Solórzano, Andrés; Encinas, Alfonso; Kramarz, Alejandro; Carrasco, Gabriel; Montoya-Sanhueza, Germán; Bobe, René
Abstract: Despite recent efforts, the diversity of Neogene mammals in Chile remains poorly known, with several presumed new taxa awaiting description. For example, previous studies have suggested that the early to late Miocene mammalian assemblages from the Laguna del Laja fossiliferous locality (Cura-Mallín and Trapa-Trapa formations), in the Andean Cordillera of south-central Chile ( 37°), comprise dozens of undescribed taxa. Therefore, a better understanding of the Laguna del Laja faunal taxonomic affinities is needed, especially because the region holds one of the few known localities spanning from early to late Miocene in Chile. Dozens of mammal specimens recently recovered in late early Miocene beds of the Cura-Mallín Formation at Laguna del Laja are described and illustrated, and a discussion of their biogeographical and paleoenvironmental significance is provided. We recognize the presence of at least 17 taxa, including some potential new ones (e.g., Maruchito sp. nov.?) and others recognized in Chile for the first time (e.g., Galileomys ). Geochronological (17.7–16.4 Ma) and biostratigraphical data indicate that this fauna correlates well with the Santacrucian SALMA, contributing to filling the gap in the taxonomic composition of Santacrucian mammalian assemblages in Chile and southwestern of South America. However, it is noteworthy that Laguna del Laja has documented some taxa previously found only in older (Colhuehuapian) and younger (Colloncuran) ages. Finally, the faunal assemblage supports a paleoenvironmental reconstruction of mixed forested and open habitats, likely with the predominance of the former, in the region during the late early Miocene and a widely distributed Santacrucian fauna throughout southern South America in both intra-arc and foreland basins. Highlights: A late early Miocene mammal assemblage of the Cura-Mallín Formation at Laguna del Laja (Chile) is analyzed. At least 17 taxa, including some potential new ones, were recognized. The mammal assemblage here studied might be related to the Santacrucian SALMA. Some of the recognized taxa shows affinities with older and younger Miocene SALMAs. The faunal assemblage supports a paleoenvironmental reconstruction of mixed forested and open habitats.